Complex crystal sand powder and preparation method thereof
Through separation and purification of bauxite and combination with multi-metal dopants, high-performance complex crystal sand powder is formed, which solves the problems of poor breathability and high production cost of existing complex crystal sand powder, and achieves the effects of high temperature stability and low linear expansion coefficient.
Patent Information
- Application Number
- CN202411821865.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing complex sand powder has poor breathability and high production costs in precision casting, making it difficult to meet the needs of high temperature stability and low linear expansion coefficient.
By separating and purifying the bauxite, and mixing it with carrageenan and tetrabutylphosphorus hydroxide, a carbon-silicon-aluminum composite material is formed, and multi-metal dopants such as nanotitanium oxide and nanoferrites and modifiers are combined to improve the sintering performance of the mold shell.
It significantly improves the high-temperature thermochemical stability, thermal shock resistance and slag corrosion resistance of complex crystal sand powder, reduces the linear expansion coefficient, and improves the breathability and surface quality of the mold shell.
Smart Images

Figure CN119634663A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of casting shell materials, and more specifically, to a complex crystal sand powder and a preparation method thereof. Background Art
[0002] Polycrystalline sand powder is a material widely used in the field of precision casting. It is made of bauxite as the base material, chemically purified, and then synthesized with other materials. It has good high-temperature stability and is not easy to react with alloy solution during casting, and will not affect the metal composition and morphology of the casting surface. At present, in some high-end precision casting fields, polycrystalline sand powder has gradually replaced other shell materials such as zircon sand.
[0003] For example, a Chinese patent application document with application publication number CN108356210A discloses a new type of complex crystal sand powder shell material and its production process, which includes the following components: Al2O3≥80%, SiO2≤18%, Fe2O3≤0.06%, and formulation ≤0.1%. It is suitable for all metal castings and alloy castings with a pouring temperature below 1750°C, such as high manganese steel, low carbon stainless steel, high temperature alloy steel, and titanium alloy. It can effectively increase the pouring temperature to ensure that the materials used in the factory are easy to handle and place, and can increase the relative mechanical strength of the cast castings, significantly reducing production costs.
[0004] For example, the Chinese patent application document with application publication number CN103030409A discloses a spherical α-alumina for investment casting shell material and its preparation method. The spherical α-alumina is: the particle shape is round and the sphericity is ≥0.9; the α-Al2O3 content is ≥99%; the refractoriness is high and is ≥1960℃. The non-spherical industrial alumina with loose structure is melted and spheroidized by high-temperature flame to obtain dense spherical α-alumina. The performance characteristics of spherical α-alumina are: round particle shape, small thermal expansion, high thermal stability and thermal shock stability, good high-temperature chemical stability, and high refractoriness. Spherical α-alumina is used for investment casting shell material, which brings beneficial effects to the casting, such as improved shell mold collapse and smooth casting surface. Although the effect of spherical α-alumina is very good, it has poor air permeability and will lead to higher production costs of shell materials.
[0005] In addition to high temperature stability, precision casting shell materials also require good air permeability, creep resistance and low linear expansion coefficient. The comprehensive performance of traditional polycrystalline sand powder has certain advantages over zircon sand or zircon powder, but in the face of the ever-developing precision casting industry, it has gradually shown its shortcomings. How to further improve the performance of polycrystalline sand powder is an issue that needs to be urgently solved in the future. Summary of the invention
[0006] In order to further improve the comprehensive application performance of complex crystal sand powder in precision casting, the present application provides a complex crystal sand powder and a preparation method thereof.
[0007] In the first aspect, the present application provides a method for preparing complex crystal sand powder, using the following technical solution:
[0008] A method for preparing complex crystal sand powder comprises the following steps:
[0009] 1) separating and purifying bauxite to obtain refined bauxite;
[0010] 2) Carrageenan and tetrabutyl phosphine hydroxide are mixed evenly, dried, calcined, and then ground to obtain a first calcined material; aluminum powder, silicon powder, and the first calcined material are mixed and ground, and then calcined in a second stage under vacuum to obtain a second calcined material;
[0011] 3) taking refined bauxite, the second calcined material, and a multi-metal doping material, mixing them evenly, and then adding a modifier and grinding them to obtain the multi-metal doping material; the multi-metal doping material is composed of at least two of nano titanium oxide, nano ferrite, nano zirconium oxide, and nano zinc oxide.
[0012] Preferably, the step 1) further includes at least one of the following technical features:
[0013] 11) The separation and purification includes acid leaching and crystallization;
[0014] 12) The refined bauxite comprises Al2O3≥82% and SiO2≤15%.
[0015] Preferably, the step 2) further includes at least one of the following technical features:
[0016] 21) The mass ratio of carrageenan to tetrabutyl phosphine hydroxide is 1:(0.15-0.2);
[0017] 22) The first stage calcination treatment is first calcined at a temperature of 1000-1100°C for 15-30 minutes, and then calcined at a temperature of 700-850°C for 2-3.5 hours;
[0018] 23) The mass ratio of aluminum powder, silicon powder and the first calcined material is 1:(0.2-0.25):(0.8-1).
[0019] Preferably, in step 3), the mass ratio of the refined bauxite, the second calcined material, and the multi-metal doped material is 1:(0.1-0.15):(0.01-0.02).
[0020] Preferably, in step 3), the modifier is prepared by the following steps:
[0021] S1: adding triethanolamine to anhydrous ethanol, mixing evenly, adding calcium chloride and barium chloride, and homogenizing to obtain a reaction solution;
[0022] S2: Introduce excess carbon dioxide into the reaction solution, then dry and grind to obtain.
[0023] Preferably, in step S1, the mass ratio of calcium chloride to barium chloride is 1:(0.35-0.5).
[0024] Preferably, the multi-metal doping material is composed of nano-titanium oxide, nano-ferrite and nano-zirconium oxide in a mass ratio of 1:0.3:0.75.
[0025] In a second aspect, the present application provides a complex crystal sand powder, which is prepared by the above-mentioned preparation method.
[0026] Preferably, the linear expansion coefficient of the complex crystal sand powder is ≤4.8*10 -6 / ℃.
[0027] Preferably, the refractoriness of the complex crystal sand powder is greater than 1800°C.
[0028] In summary, this application has the following beneficial effects:
[0029] 1. The present application uses bauxite as the initial raw material, and after separation and purification, the second calcined material and the multi-metal doping material are added to obtain the complex crystal sand powder, which is a high-end precision casting shell material with stable and consistent crystal structure, large elastic modulus, high decomposition temperature, good high-temperature thermochemical stability, and small high-temperature creep. In addition, the complex crystal sand powder of the present application also has a low linear expansion coefficient, high true porosity after sintering, and high slag corrosion resistance and thermal shock resistance.
[0030] 2. In this application, carrageenan is mixed with tetrabutylphosphorus hydroxide and calcined to obtain a carbon precursor with sulfur defects and phosphorus defects, which is then mixed with aluminum powder and silicon powder and calcined in vacuum. Aluminum atoms and silicon atoms form a carbon-silicon-aluminum composite material in the carbon precursor, and during the calcination process, the sulfur defects and phosphorus defects in the carbon precursor play a certain catalytic role, regulating and promoting the formation of the carbon-silicon-aluminum composite material. When the second calcined material is compounded with bauxite, the heat dissipation and air permeability of the mold shell after sintering can be improved, and oxidation can also be blocked, so that pitting, black spots and other defects are not easy to occur on the surface of the casting.
[0031] 3. The present application further adds multi-metal doping materials and modifiers on the basis of refined bauxite and the second calcined material. The multi-metal doping materials can produce the migration of metal atoms during the sintering and casting process of the mold shell, can form infiltration doping on the surface of the complex crystal sand powder, cause lattice distortion, and form a more stable crystal structure, and have a stronger ability to block oxidation of the casting surface, and improve thermal shock resistance and slag corrosion resistance. At the same time, the air permeability is also better, and pores are not easy to appear on the casting surface. The modifier of the present application is calcium chloride and barium chloride as template agents. Under the action of first end-capping and then decapping of triethylamine, an inorganic cross-linked body of calcium carbonate and barium carbonate is formed. During the casting process, crystal epitaxial growth can be formed on the surface of the complex crystal sand powder, and the stability of the crystal structure during the casting process can be improved. The true porosity of the refractory layer formed during the sintering process is high, which improves the air permeability of the mold shell and is conducive to the collapse and sand cleaning of the mold shell after casting. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is the XRD diagram of the complex crystal sand powder of Examples 1-3 of the present application.
[0033] Figure 2 It is the XRD diagram of the complex crystal sand powder of comparative examples 1-3 of the present application.
[0034] Figure 3 It is a schematic diagram of the true porosity of the refractory layer of the complex sand powder mold shell of Examples 1-3 and Comparative Examples 1-3 of the present application.
[0035] Figure 4 It is a schematic diagram of the linear expansion coefficient of the refractory layer of the complex sand powder shell of Examples 1-3 and Comparative Examples 1-3 of the present application.
[0036] Figure 5 This is the SEM image of the casting surface of Example 3.
[0037] Figure 6 is a cross-sectional micrograph of the casting of Example 3. DETAILED DESCRIPTION
[0038] The present application is further described in detail below with reference to the embodiments.
[0039] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0040] The present application provides a complex crystal sand powder and a preparation method thereof. The complex crystal sand powder prepared in the present application can be used for all metal castings and alloy castings thereof with a pouring temperature below 1750°C, such as high manganese steel, low carbon stainless steel, high temperature alloy steel, titanium alloy, etc.
[0041] The preparation method of the composite sand powder of the present application comprises the following steps:
[0042] 1) separating and purifying bauxite to obtain refined bauxite;
[0043] 2) Carrageenan and tetrabutyl phosphine hydroxide are mixed evenly, dried, calcined, and then ground to obtain a first calcined material; aluminum powder, silicon powder, and the first calcined material are mixed and ground, and then calcined in a second stage under vacuum to obtain a second calcined material;
[0044] 3) taking refined bauxite, the second calcined material, and a multi-metal doping material, mixing them evenly, and then adding a modifier and grinding them to obtain the multi-metal doping material; the multi-metal doping material is composed of at least two of nano titanium oxide, nano ferrite, nano zirconium oxide, and nano zinc oxide.
[0045] In step 2) of the method for preparing complex crystal sand powder of the present application, the mass ratio of carrageenan to tetrabutyl phosphonium hydroxide is 1:1:(0.15-0.2). In some specific embodiments, the mass ratio of carrageenan to tetrabutyl phosphonium hydroxide is 1:0.15, 1:0.155, 1:0.16, 1:0.165, 1:0.17, 1:0.175, 1:0.18, 1:0.185, 1:0.19, 1:0.195, 1:0.2.
[0046] In step 2) of the method for preparing complex crystal sand powder of the present application, the first calcination treatment is first calcined at a temperature of 1000-1100°C for 15-30min, and then calcined at a temperature of 700-850°C for 2-5h. In some specific embodiments, the first calcination treatment is first calcined at a temperature of 1000°C, 1030°C, 1050°C, 1100°C for 15min, 20min, 25min, 30min, and then calcined at a temperature of 700°C, 750°C, 800°C, 850°C for 2h, 2.5h, 3h, 3.5h.
[0047] In step 2) of the method for preparing complex crystal sand powder of the present application, the mass ratio of aluminum powder, silicon powder and the first calcined material is 1:(0.2-0.25):(0.8-1). In some specific embodiments, the mass ratio of aluminum powder, silicon powder and the first calcined material is 1:0.2:0.8, 1:0.22:0.8, 1:0.24:0.8, 1:0.2:0.85, 1:0.2:0.9, 1:0.2:0.95, 1:0.2:0.85, 1:0.22:0.85, 1:0.24:0.85, 1:0.22:0.9, 1:0.24:0.9, 1:0.22:0.95, 1:0.24:0.95, 1:0.25:1.
[0048] In step 2) of the method for preparing complex crystal sand powder of the present application, the average particle size of the first calcined material is 50-200 μm. The average particle size of the second calcined material is 200-500 μm. Optionally, the average particle size of the first calcined material is 50-100 μm, 100-150 μm, or 150-200 μm, etc. Optionally, the average particle size of the second calcined material is 200-300 μm, 300-400 μm, or 400-500 μm, etc. In some specific embodiments, the average particle size of the first calcined material may be 50 μm, 100 μm, 150 μm, or 200 μm. The average particle size of the second calcined material may be 200 μm, 300 μm, 400 μm, or 500 μm.
[0049] In step 3) of the method for preparing complex crystal sand powder of the present application, the mass ratio of refined bauxite, the second calcined material, and the multi-metal doping material is 1:(0.1-0.15):(0.01-0.02). In some specific embodiments, the mass ratio of refined bauxite, the second calcined material, and the multi-metal doping material is 1:0.12:0.01, 1:0.135:0.01, 1:0.15:0.01, 1:0.15:0.01, 1:0.15:0.015, 1:0.15:0.02, 1:0.13:0.01, 1:0.13:0.015, 1:0.13:0.02.
[0050] In step 3) of the method for preparing complex crystal sand powder of the present application, the amount of the modifier added is 0.2-0.5% of the mass of the refined bauxite. In some specific embodiments, the amount of the modifier added is 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5% of the mass of the refined bauxite.
[0051] In step S1 of the present application, the mass ratio of calcium chloride to barium chloride is 1:(0.35-0.5). In some specific embodiments, the mass ratio of calcium chloride to barium chloride can be 1:0.35, 1:0.4, 1:0.45, 1:0.5.
[0052] Example 1
[0053] The preparation method of the composite sand powder of this embodiment comprises the following steps:
[0054] 1) Adding bauxite into a centrifuge, then adding dilute sulfuric acid and hydroxyproline, stirring and impregnating, centrifuging to separate solid and liquid to obtain a centrifuge liquid, then neutralizing and concentrating the centrifuge liquid, washing the crystals, and drying to obtain refined bauxite;
[0055] 2) adding carrageenan and tetrabutyl phosphine hydroxide into a stirring kettle and mixing them evenly, and after drying, performing a first-stage calcination treatment at a temperature of 1000° C. for 1 hour; then grinding in a ball mill to obtain a first calcined material with an average particle size of 200 μm; mixing aluminum powder, silicon powder, and the first calcined material in a mass ratio of 1:0.22:0.85 and grinding, and then performing a second-stage calcination treatment in a vacuum calcining furnace at a calcination temperature of 1550° C. for 2 hours, and grinding to obtain a second calcined material with an average particle size of 500 μm;
[0056] 3) Add refined bauxite, the second calcined material, and the multi-metal doping material into a ball mill, mix them evenly, then add the modifier and grind to obtain the product.
[0057] The amount of hydroxyproline added is 0.5% of the mass of bauxite. The mass ratio of carrageenan to tetrabutyl phosphine hydroxide is 1:0.175. In the components of refined bauxite, Al2O3≥82% and SiO2≤15%. The mass ratio of refined bauxite, second calcined material and multi-metal doping material is 1:0.1:0.02. The multi-metal doping material is composed of nano titanium oxide and nano ferrite in a mass ratio of 1:2. The modifier is nano calcium carbonate, and the amount of the modifier added is 0.5% of the mass of refined bauxite.
[0058] The composite sand powder of this embodiment is prepared by the above-mentioned preparation method, and the linear expansion coefficient of the composite sand powder is ≤4.8*10 -6 / ℃, the refractoriness of complex crystal sand powder is >1800℃.
[0059] Example 2
[0060] The preparation method of the composite sand powder of this embodiment comprises the following steps:
[0061] 1) Adding bauxite into a centrifuge, then adding dilute sulfuric acid and hydroxyproline, stirring and impregnating, centrifuging to separate solid and liquid to obtain a centrifuge liquid, then neutralizing and concentrating the centrifuge liquid, washing the crystals, and drying to obtain refined bauxite;
[0062] 2) adding carrageenan and tetrabutyl phosphine hydroxide into a stirring kettle and mixing them evenly, and after drying, calcining them at 1100° C. for 15 min, and then calcining them at 850° C. for 2 h; then grinding them in a ball mill to obtain a first calcined material with an average particle size of 50 μm; mixing aluminum powder, silicon powder and the first calcined material in a mass ratio of 1:0.22:0.85 and grinding them, and then performing a two-stage calcination treatment in a vacuum calcining furnace at a calcination temperature of 1550° C. for 2 h, and grinding them to obtain a second calcined material with an average particle size of 200 μm;
[0063] 3) Add refined bauxite, the second calcined material, and the multi-metal doping material into a ball mill, mix them evenly, then add the modifier and grind to obtain the product.
[0064] The modifier of this embodiment is prepared by the following steps:
[0065] S1: add anhydrous ethanol into a beaker, add triethanolamine while stirring continuously, the volume ratio of anhydrous ethanol to triethanolamine is 3:1, mix well, add calcium chloride until the calcium chloride is saturated and dissolved, then add barium chloride, and homogenize to obtain a reaction solution;
[0066] S2: Introduce excess carbon dioxide into the reaction solution, then dry and remove the wastewater ethanol and triethanolamine and recover them after grinding.
[0067] The amount of hydroxyproline added is 0.5% of the mass of bauxite. The mass ratio of carrageenan to tetrabutyl phosphine hydroxide is 1:0.175. Among the components of refined bauxite, Al2O3 ≥ 82%, SiO2 ≤ 15%. The mass ratio of refined bauxite, second calcined material, and multi-metal doping material is 1:0.1:0.02. The multi-metal doping material is composed of nano titanium oxide, nano ferrite, and nano zirconium oxide in a mass ratio of 1:0.3:0.75. The mass ratio of calcium chloride to barium chloride is 1:0.5. The amount of modifier added is 0.2% of the mass of refined bauxite.
[0068] The composite sand powder of this embodiment is prepared by the above-mentioned preparation method, and the linear expansion coefficient of the composite sand powder is ≤4.8*10 -6 / ℃, the refractoriness of complex crystal sand powder is >1800℃.
[0069] Example 3
[0070] The preparation method of the composite sand powder of this embodiment comprises the following steps:
[0071] 1) Adding bauxite into a centrifuge, then adding dilute sulfuric acid and hydroxyproline, stirring and impregnating, centrifuging to separate solid and liquid to obtain a centrifuge liquid, then neutralizing and concentrating the centrifuge liquid, washing the crystals, and drying to obtain refined bauxite;
[0072] 2) adding carrageenan and tetrabutyl phosphine hydroxide into a stirring kettle and mixing them evenly, and after drying, calcining them at 1000° C. for 30 min, and then calcining them at 700° C. for 3.5 h; then grinding them in a ball mill to obtain a first calcined material with an average particle size of 100 μm; mixing and grinding aluminum powder, silicon powder and the first calcined material in a mass ratio of 1:0.22:0.85, and then performing a two-stage calcination treatment in a vacuum calcining furnace at a calcination temperature of 1550° C. for 2 h, and grinding to obtain a second calcined material with an average particle size of 300 μm;
[0073] 3) Add refined bauxite, the second calcined material, and the multi-metal doping material into a ball mill, mix them evenly, then add the modifier and grind to obtain the product.
[0074] The modifier of this embodiment is prepared by the following steps:
[0075] S1: add anhydrous ethanol into a beaker, add triethanolamine while stirring continuously, the volume ratio of anhydrous ethanol to triethanolamine is 3:1, mix well, add calcium chloride until the calcium chloride is saturated and dissolved, then add barium chloride, and homogenize to obtain a reaction solution;
[0076] S2: Introduce excess carbon dioxide into the reaction solution, then dry and remove the wastewater ethanol and triethanolamine and recover them after grinding.
[0077] The amount of hydroxyproline added is 0.5% of the mass of bauxite. The mass ratio of carrageenan to tetrabutyl phosphine hydroxide is 1:0.175. Among the components of refined bauxite, Al2O3 ≥ 82% and SiO2 ≤ 15%. The mass ratio of refined bauxite, second calcined material, and multi-metal doping material is 1:0.15:0.01. The multi-metal doping material is composed of nano titanium oxide, nano ferrite, and nano zirconium oxide in a mass ratio of 1:0.3:0.75. The mass ratio of calcium chloride to barium chloride is 1:0.35. The amount of modifier added is 0.5% of the mass of refined bauxite.
[0078] The composite sand powder of this embodiment is prepared by the above-mentioned preparation method, and the linear expansion coefficient of the composite sand powder is ≤4.8*10 -6 / ℃, the refractoriness of complex crystal sand powder is >1800℃.
[0079] Comparative Example 1
[0080] The preparation method of the complex crystal sand powder of this comparative example comprises the following steps: adding refined bauxite and iron oxide into a ball mill, mixing and grinding, melting at high temperature, and then cooling, crushing and grinding to obtain the complex crystal sand powder.
[0081] The refined bauxite has Al2O3≥82% and SiO2≤15%. The mass ratio of the refined bauxite to iron oxide is 1:0.02.
[0082] The preparation method of the complex crystal sand powder of this comparative example is prepared by the above-mentioned preparation method.
[0083] Comparative Example 2
[0084] The preparation method of the composite sand powder of this embodiment of the comparative example comprises the following steps:
[0085] 1) Adding bauxite into a centrifuge, then adding dilute sulfuric acid and hydroxyproline, stirring and impregnating, centrifuging to separate solid and liquid to obtain a centrifuge liquid, then neutralizing and concentrating the centrifuge liquid, washing the crystals, and drying to obtain refined bauxite;
[0086] 2) Aluminum powder, silicon powder and carbon powder were mixed and ground in a mass ratio of 1:0.22:0.85, and then calcined in a vacuum calcining furnace at a calcination temperature of 1550° C. for 2 h to obtain a calcined material with an average particle size of 300 μm;
[0087] 3) Add refined bauxite, calcined material and multi-metal doping material into a ball mill, mix well, add a modifier and grind to obtain the product.
[0088] The modifier of this comparative example is prepared by the following steps:
[0089] S1: add anhydrous ethanol into a beaker, add triethanolamine while stirring continuously, the volume ratio of anhydrous ethanol to triethanolamine is 3:1, mix well, add calcium chloride until the calcium chloride is saturated and dissolved, then add barium chloride, and homogenize to obtain a reaction solution;
[0090] S2: Introduce excess carbon dioxide into the reaction solution, then dry and remove the wastewater ethanol and triethanolamine and recover them after grinding.
[0091] The amount of hydroxyproline added is 0.5% of the mass of bauxite. The mass ratio of carrageenan to tetrabutyl phosphine hydroxide is 1:0.175. Among the components of refined bauxite, Al2O3 ≥ 82% and SiO2 ≤ 15%. The mass ratio of refined bauxite, second calcined material, and multi-metal doping material is 1:0.15:0.01. The multi-metal doping material is composed of nano titanium oxide, nano ferrite, and nano zirconium oxide in a mass ratio of 1:0.3:0.75. The mass ratio of calcium chloride to barium chloride is 1:0.35. The amount of modifier added is 0.5% of the mass of refined bauxite.
[0092] The complex crystal sand powder of this comparative example is prepared by adopting the above-mentioned preparation method.
[0093] Comparative Example 3
[0094] The preparation method of the complex crystal sand powder of this comparative example comprises the following steps:
[0095] 1) Adding bauxite into a centrifuge, then adding dilute sulfuric acid and hydroxyproline, stirring and impregnating, centrifuging to separate solid and liquid to obtain a centrifuge liquid, then neutralizing and concentrating the centrifuge liquid, washing the crystals, and drying to obtain refined bauxite;
[0096] 2) adding carrageenan and tetrabutyl phosphine hydroxide into a stirring kettle and mixing them evenly, calcining them at 1000° C. for 30 min after drying, and then calcining them at 700° C. for 3.5 h; and then grinding them in a ball mill to obtain a first calcined material with an average particle size of 100 μm;
[0097] 3) Add refined bauxite and the first calcined material into a ball mill, mix them evenly and grind them to obtain the product.
[0098] The amount of hydroxyproline added is 0.5% of the mass of bauxite. The mass ratio of carrageenan to tetrabutyl phosphine hydroxide is 1:0.175. Among the components of refined bauxite, Al2O3≥82% and SiO2≤15%. The mass ratio of refined bauxite to the first calcined material is 1:0.15.
[0099] The complex crystal sand powder of this comparative example is prepared by adopting the above-mentioned preparation method.
[0100] Performance testing
[0101] The composite sand powders of Examples 1-3 and Comparative Examples 1-3 were subjected to XRD testing. The test results are as follows: Figure 1 and Figure 2 shown.
[0102] The composite sand powder of Examples 1-3 and Comparative Examples 1-3 was used for casting tests, wherein the surface material was composite sand powder, the powder-liquid ratio was 2.6:1, the viscosity was 38±2(s), the surface drying temperature was 23±2°C, and the drying time was 3h. The shell roasting temperature was 1150±30°C, the molten steel pouring temperature was 1100°C, the box was not covered, and the molten steel material was 430# stainless steel. According to GB / T2997-2015, the true porosity and linear expansion coefficient of the shell refractory layer during casting were tested. The test data are as follows: Figure 3 and Figure 4 The SEM image of the casting surface of Example 3 is shown in Figure 5 The cross-sectional micrograph of the casting of Example 3 is shown in FIG. Figure 6 shown.
[0103] Analyze Examples 1-3 and Comparative Examples 1-3 and combine Figure 1-5 It can be seen that the composite sand powder of the present application has very good high-temperature thermochemical stability in precision casting applications, good heat dissipation and air permeability, and can effectively block oxidation without covering the box. Moreover, under the same conditions, the dosage is small, the slag corrosion resistance and thermal shock resistance are strong, the casting surface is smooth and beautiful, and it is not easy to have pits, pits and black spots. The product appearance and overall quality of the casting are very good.
[0104] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing complex crystal sand powder, characterized in that: The steps include: 1) separating and purifying bauxite to obtain refined bauxite; 2) Carrageenan and tetrabutyl phosphine hydroxide are mixed evenly, dried, and then subjected to a first-stage calcination treatment, and then ground to obtain a first calcined material; aluminum powder, silicon powder, and the first calcined material are mixed and ground, and then subjected to a second-stage calcination treatment under vacuum, Grinding to obtain a second calcined material; 3) taking refined bauxite, the second calcined material, and a multi-metal doping material and mixing them evenly, and then adding a modifier and grinding them to obtain the multi-metal doping material; the multi-metal doping material is composed of at least two of nano titanium oxide, nano ferrite, nano zirconium oxide, and nano zinc oxide.
2. The method for preparing a complex crystal sand powder according to claim 1, characterized in that: In the step 1), at least one of the following technical features is also included: 11) The separation and purification includes acid leaching and crystallization; 12) The refined bauxite comprises Al2O3≥82% and SiO2≤15%.
3. The method for preparing a complex crystal sand powder according to claim 1, characterized in that: In the step 2), at least one of the following technical features is also included: 21) The mass ratio of carrageenan to tetrabutyl phosphine hydroxide is 1:(0.15-0.2); 22) The first stage calcination treatment is first calcined at a temperature of 1000-1100°C for 15-30 minutes, and then calcined at a temperature of 700-850°C for 2-3.5 hours; 23) The mass ratio of aluminum powder, silicon powder and the first calcined material is 1:(0.2-0.25):(0.8-1).
4. The method for preparing a complex crystal sand powder according to claim 1, characterized in that: In the step 3), the mass ratio of the refined bauxite, the second calcined material, and the multi-metal doped material is 1:(0.1-0.15):(0.01-0.02).
5. The method for preparing a complex crystal sand powder according to claim 1, characterized in that: In the step 3), the modifier is prepared by the following steps: S1: adding triethanolamine to anhydrous ethanol, mixing evenly, adding calcium chloride and barium chloride, and homogenizing to obtain a reaction solution; S2: Introduce excess carbon dioxide into the reaction solution, then dry and grind to obtain.
6. The method for preparing complex crystal sand powder according to claim 5, characterized in that: In the step S1, the mass ratio of calcium chloride to barium chloride is 1:(0.35-0.5).
7. The method for preparing a complex crystal sand powder according to claim 1, characterized in that: The multi-element metal doping material is composed of nano titanium oxide, nano ferrite and nano zirconium oxide in a mass ratio of 1:0.3:0.
75.
8. A complex crystal sand powder, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. The complex crystal sand powder according to claim 8, characterized in that: The linear expansion coefficient of the complex crystal sand powder is ≤4.8*10 -6 / ℃.
10. The complex crystal sand powder according to claim 8, characterized in that: The refractoriness of the complex crystal sand powder is greater than 1800°C.
Citation Information
Patent Citations
Spherical alpha-alumina for shell manufacturing material for investment casting, and preparation method thereof
CN103030409A
Novel compound crystal sand powder shell-making material and production technology thereof
CN108356210A
Sand for precision casting and preparation method thereof
CN113800927A
High-precision precoated sand and preparation method and application thereof
CN116372095A
Silicon carbide-containing mold and facecoat compositions and methods for casting titanium and titanium aluminide alloys
US20150147186A1